Implementation of Juvenile Reprimand in Indonesia - Sarwirini Sarwirini; Trian Diarsa (Universitas Airlangga, 2023)
Eight years on from the enactment of Law of The Republic Indonesia No. 11 of 2012 concerning the Juvenile Criminal Justice System, there is no implementing regulation that regulates the reprimand sanction imposed on children. In other countries, for example in the United States, a reprimand is called a judicial warning or reprimand and is implemented in front of a public trial by a judge, who verbally warns children, following which they are returned to their parents and have no obligation that must be met regarding the criminal acts they have committed. This type of penalty is mostly imposed on a juvenile who is guilty of their first offence, as well as against non-violent crimes. The placement of the reprimand in Article 77 Paragraph (1) of JCJS Act is not without purpose, but this is a form of protection for children of criminal offenders and provides choices for judges in imposing sanctions other than imprisonment. Using normative legal methods, this research examines the current practice of implementing the reprimand sanction and proposes possible suggestions for its improvement.